Improving the Growth of Tomato Plants (Lycopersicum esculentum L.) by Providing Ash from Empty Oil Palm Fruit Bunches - Ferdinan Luki Alamsyah; Khairul Rizal; Novilda Elizabeth Mustamu; Ika Ayu Putri Septyani (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Tomato plants (Lycopersicon esculentum L.) are among the most widely consumed vegetables worldwide and belong to the Solanaceae family. They represent a vegetable commodity with significant potential for development. This study aims to evaluate the effect of applying empty oil palm bunch ash (ATKKS) on the growth of tomato plants. The research employed a non-factorial Randomized Block Design (RBD) with four treatments and five replications. Data were analyzed using Analysis of Variance (ANOVA), followed by a 5% Duncan's Multiple Range Test (DMRT) for further comparison. The results showed that the Sand Soil Treatment combined with 450 grams of Empty Oil Palm Bunch Ash per polybag was the most effective in promoting vegetative growth. This yield was evidenced by a significant increase in plant height, number of leaves, and stem diameter compared to other treatments. This finding indicates that the combination can optimally supply the nutrients required by plants up to the fourth week. For future research, it is recommended to evaluate the effects of this treatment during the generative phase of plant development and on production yields. Additionally, assessing its effectiveness on other plant species and under various environmental conditions will help broaden its practical application in the field.